2005
DOI: 10.1111/j.1742-4658.2005.04823.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression analysis and functional confirmation of ecdysone receptor and ultraspiracle from the Colorado potato beetle Leptinotarsa decemlineata

Abstract: The growth of insects progresses via unique physiological events such as molting and metamorphosis. Those processes are strictly regulated by two peripheral hormones, molting hormone (20-hydroxyecdysone; 20E) and juvenile hormone (JH). 20E controls transcription of target genes by interacting with molting hormone receptor proteins, which bind to ecdysone response elements (EcREs) located upstream of the target genes. The transcriptional activation by 20E triggers signal cascades, and the development is accompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 78 publications
8
79
3
Order By: Relevance
“…The EcRA specific sequence from T. castaneum also showed a similarity with EcRA isoform-specific sequences identified in Choristoneura fumiferana (Perera et al 1999), Bombyx mori (Kamimura et al, 1997), Aedes aegypti (Wang et al, 2002), Drosophila melanogaster (Talbot et al, 1993) and Locusta migratoria (Saleh et al, 1998). The EcRB isoform-specific region contained 96 amino acids and these amino acids showed the highest similarity with the amino acids identified in the EcRB isoform of Leptinotarsa decemlineata (Ogura et al 2005). As shown in Table 1, the amino acids identified in the EcRB isoform-specific region of T. castaneum also showed a similarity with the amino acids identified in the EcRB isoforms of Tenebrio molitor (Mouillet et al, 1997), Celuca pugilator (Chung et al, 1998) and Daphnia magna (Accession # AB274824.1).…”
Section: Ecr and Usp Sequencesmentioning
confidence: 62%
See 1 more Smart Citation
“…The EcRA specific sequence from T. castaneum also showed a similarity with EcRA isoform-specific sequences identified in Choristoneura fumiferana (Perera et al 1999), Bombyx mori (Kamimura et al, 1997), Aedes aegypti (Wang et al, 2002), Drosophila melanogaster (Talbot et al, 1993) and Locusta migratoria (Saleh et al, 1998). The EcRB isoform-specific region contained 96 amino acids and these amino acids showed the highest similarity with the amino acids identified in the EcRB isoform of Leptinotarsa decemlineata (Ogura et al 2005). As shown in Table 1, the amino acids identified in the EcRB isoform-specific region of T. castaneum also showed a similarity with the amino acids identified in the EcRB isoforms of Tenebrio molitor (Mouillet et al, 1997), Celuca pugilator (Chung et al, 1998) and Daphnia magna (Accession # AB274824.1).…”
Section: Ecr and Usp Sequencesmentioning
confidence: 62%
“…Analysis of sequences showed that EcR gene from T. castaneum codes for two isoforms that contain different amino terminal A/B domain and a common region containing CDEF domains. EcRA specific region contained 160 amino acids and showed the highest similarity with EcRA isoform cloned form Leptinotarsa decemlineata (Table 1) (Ogura et al 2005). The EcRA specific sequence from T. castaneum also showed a similarity with EcRA isoform-specific sequences identified in Choristoneura fumiferana (Perera et al 1999), Bombyx mori (Kamimura et al, 1997), Aedes aegypti (Wang et al, 2002), Drosophila melanogaster (Talbot et al, 1993) and Locusta migratoria (Saleh et al, 1998).…”
Section: Ecr and Usp Sequencesmentioning
confidence: 86%
“…Total RNA was extracted using TRIzol (Life Technologies) as described previously. 27) cDNAs of EcRs and USPs were synthesized from total RNA with a Ready-To-Go T-Primed FirstStrand Kit (GE Healthcare). Reverse transcription polymerase chain reaction (RT-PCR) was performed with degenerate primers designed in our previous study.…”
Section: Chemicalsmentioning
confidence: 99%
“…Reverse transcription polymerase chain reaction (RT-PCR) was performed with degenerate primers designed in our previous study. 27,28) To amplify EcR from H. axyridis, the first PCR was performed using EcR-F1 and EcR-R2 primers with the annealing temperature of 48°C. To conduct the second and the third PCRs (nested PCR), EcR-F2/ R2 and EcR-F3/R3 primers were used with the annealing temperatures of 52°C and 46°C, respectively.…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation